Seeking the legitimation of mainstream journalism: A portuguese case-study - Álvares, C.; Cardoso, G.; Crespo, M.; Pinto-Martinho, A. (Journalism Practice, 2023)
This article consists in a case-study of the Portuguese site Notícias Viriato (NV), which has controversially been registered by the Portuguese Regulatory Authority (ERC) as a ‘general information’ site, officially recognised as drawing close to mainstream journalism in a context of accusations of rightwing bias. We will argue that NV’s registration with ERC marks a new phase for the far right in the Portuguese political and journalistic spheres, due to grounding legitimation in the Constitutional right to freedom of expression. By drawing close to officialdom, this news site bypasses the inexistence, in the Portuguese juridical framework, of advocacy journalism. According to the Portuguese Constitution, partisanship excludes journalistic activity, with journalism being of an ‘informative’, and therefore objective, nature. While the dangers of partisanship are recognised, the existence of an advocacy continuum within journalism are ignored. In a digital era in which journalistic objectivity has ceased to be the norm, the labelling of journalism as ‘general information’, defined against ‘partisanship’, is incapable of responding to the challenges posed by alternative media in redefining professional journalism. This demonstrates the need to update both the Portuguese Constitution and prevalent media legislation to accompany changing times.